Issues and Failure of Infrastructure Project Implementation in Nigeria - Okolie, Ugo Chuks; Edo, Zephaniah Osuyi (Universitas PGRI Madiun, 2023)
Governments and organizations, particularly those in developing nations, have experienced project failures during the implementation of their projects, though there may be some variations among governments in the causes, effects, and consequences of such failures. The purpose of this study was to look into the reasons behind project failures in developing nations, specifically looking at Nigeria. As a result, the implementation of infrastructure projects in Nigeria has encountered problems and failed. The investigation is a documentary study. It obtains its data from secondary sources, such as books, journals, government-issued documents, newspapers, magazines, and websites that host related data. The collected data were examined using a content analysis technique. It became clear that project failure occurs frequently in developing nations, particularly Nigeria, and that there are a variety of causes, effects, and consequences. Poor financial capability, inaccurate costing, corruption, incompetence and a lack of knowledge, poor planning and estimation, poor contracting and contractor practices, poor communication, frequent design scope changes and errors, poor leadership, interference from socio-cultural and political factors, and poor knowledge were some of the causes identified. The effects of project failure were found to include lost of state revenue, citizen revenue losses, project cost overruns, low community empowerment and poor infrastructure. Slow economic growth, sector-focused underdevelopment, a loss of foreign aid and grants, stricter donor regulations, the loss of elections to the incumbent leadership, and a lack of trust from financial institutions in the government were the results. This study suggests, among other things, that pertinent government agencies, such as the National Council on Public Procurement, Bureau of Public Procurement, and Due Process Office, which are in charge of overseeing and monitoring federal government projects nationwide, be cleaned up and redesigned to best carry out their duties without using unethical methods.